Antimicrobial properties of Camellia oleifera oil - Estevinho, Leticia M. (2012)
Camellias have been used in oriental ethnomedicine and appear very promising for pharmaceutical exploitation since modern science has made it possible to specify their potential medical significance with antimicrobial, antioxidant, antiallergic, antiviral and skin healing properties. In the present study oil obtained from seeds of Camellia oleifera was studied for its antimicrobial activity using clinically isolated bacterial and yeast strains. The oil evidenced antimicrobial activity, and showed different selectivity and MICs for each microorganism tested. Obtained results indicate that the tested oil acted best in relation to Gram (-) bacteria than Gram (+). The data obtained in the in vitro models clearly establish its antimicrobial potency.